2014
DOI: 10.1111/trf.12663
|View full text |Cite
|
Sign up to set email alerts
|

Immune globulins and same‐day thrombotic events as recorded in a large health care database during 2008 to 2012

Abstract: Our claims-based cohort study suggests a potentially elevated TE risk with different IG products and shows importance of recipient factors such as older age, previous TE, hypercoagulable state(s), and other health conditions. The results of this study suggest the need for continuous evaluation of procoagulant activity and manufacturing processes for IG products to further assure their safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…13,14,[24][25][26][27][28][29][30][31][32] However, the extent to which these events are attributable to the IVIg itself rather than other risk factors is unclear, as is the risk associated with low doses of IVIg for immunodeficiency. In this retrospective cohort study, we assessed rates of clinically serious arterial and venous TEEs in older patients with CLL or MM who initiated IVIg therapy.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,[24][25][26][27][28][29][30][31][32] However, the extent to which these events are attributable to the IVIg itself rather than other risk factors is unclear, as is the risk associated with low doses of IVIg for immunodeficiency. In this retrospective cohort study, we assessed rates of clinically serious arterial and venous TEEs in older patients with CLL or MM who initiated IVIg therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary data from the overall analysis showed that ADRs occurred least frequently in patients with ITP and most frequently in patients with secondary immunodeficiency (case incidence of 2.1%), despite these patients being treated at the lowest dose (mean 0.2 g/ kg at a median maximum infusion rate of 3.3 mL/kg/ h). Such observations suggest that the occurrence of ADRs is influenced by multiple factors, which may include IVIG infusion history, underlying disease and general condition of the patient, and is not solely related to dose or the rate of infusion [10,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…IVIG can increase blood viscosity and impair blood flow, thereby increasing the risk of TEEs in patients with pre-existing risk factors, such as advanced age, immobilisation, diabetes mellitus, hypertension and a history of vascular disease or TEEs, so caution should be exercised when using IVIG products in such patients [18][19][20]. In patients at risk of TEEs, IVIG products should be administered at the minimum rate of infusion and dose practicable [17,20]. In our subgroup of 112 patients with ITP, there were no TEEs reported in association with 626 infusions of octagam® 10%, with a mean dose of 0.4 g/kg per infusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations